The Influence of Social Media as a Tourism Marketing Tool in Negros Oriental, Philippines - Tayco, Ryan; Tubog, Millard Vaughn; Zamora, Glennen (Journal of Interdisciplinary Perspectives, 2024)
The study aimed to determine the influence of social media as a tourism marketing tool for Negros Oriental as a tourist destination. Utilizing a descriptive method and a correlational technique, this research focused on both local and foreign tourists visiting Negros Oriental. A total of 392 tourists were selected through convenience sampling to participate as respondents. Results indicate that the majority of respondents are female, unmarried, aged between 18 and 30, and heavily rely on social media for information, particularly when planning activities and trips. A significant portion of respondents are college-educated Filipinos, who spend an average of 4 hours and 15 minutes daily on social media. Most respondents are employed and use social media for both professional and personal purposes. Findings reveal that most travelers visit Negros Oriental for relaxation and extensively use smartphones for travel-related purposes. Facebook emerged as the most commonly used platform, significantly influencing travel decisions and planning. Socio-demographic factors such as age, gender, civil status, educational level, and occupation were found to influence social media usage patterns and travel decisions. The study concludes that social media is an effective tourism marketing tool, capable of influencing tourists' decisions regarding their visits to tourist destinations.